Google Classroom Sebagai Media Pembelajaran Sejarah Alternatif Selama Covid-19 - Sayuti, Hilya Azizah; Abbas, Ersis Warmansyah; Prawitasari, Melisa; Akmal, Helmi (Lambung Mangkurat University, 2023)
As a result of the Covid-19 epidemic in Indonesia, all activities are now carried out from home, which means that in the field of education, all teachers must design teaching media that students can use from home. The goal of this research is to describe how Google Classroom is being used in historical learning to combat the spread of Covid-19 in schools. This is a qualitative study using descriptive methods with primary and secondary data as data sources. Interview, observation, and documentation procedures are used in data collection. Google Classroom is an interactive learning media based on e-learning that makes it easier for teachers and students to complete the teaching and learning process at home to assist learning based on information and communication technology. Google Classroom is currently incredibly effective and efficient, and it is not constrained by space or time. Teachers can provide students with materials in the form of text, images, audio, and video via the internet. Additionally, teachers can use a link from a Google Form filed in Google Classroom to create a list of students present.